Choix moraux, éthique et jeux vidéos - Antoine Rocipon (Conserveries Mémorielles)
All videogames are about choice. Fighting or hiding ? Jumping or kneeling ? Left or right ? Some games go further : they offer the player the possibility to make choices that will change the story, sometimes by the way of moral dilemnas : will my character kill or spare the criminal he has been tracking during all the game ? Should I try to save this stranger and risk losing some precious ressources by doing that ? When he takes this kind of decision, the player also question his morality and his responsability in both the virtual and the real world. By doing that, videogames are changing our relation to ethic.